2014
DOI: 10.1007/s00213-014-3473-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repeated zolpidem treatment on tolerance, withdrawal-like symptoms, and GABAA receptor mRNAs profile expression in mice: Comparison with diazepam

Abstract: In mice, subchronic treatment of zolpidem and diazepam can produce deficits in the locomotor-impairing effects of zolpidem, anxiety-like withdrawal symptoms, and subunit-specific mRNA changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…From a therapeutic standpoint, these overlapping, yet distinct mechanisms have important implications regarding tolerance and dependence. GABA A receptor modulators have been shown in both animal models and human subjects to exhibit tolerance to repetitive dosing, becoming less efficacious over time [ 43 45 ], while ORAs, including suvorexant (Belsomra®), have shown no tolerance or evidence of withdrawal even after a year of treatment in patients [ 17 ] and no diminution of efficacy in animal models (reviewed in [ 46 ]). While the role of orexin in reward and withdrawal suggest that ORAs may have the capacity to diminish the dependence on rewarding influences (reviewed in [ 47 ]), the effectiveness of ORAs in animal models and human subjects following treatment with the current standard of care, GABA A receptor modulators, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic standpoint, these overlapping, yet distinct mechanisms have important implications regarding tolerance and dependence. GABA A receptor modulators have been shown in both animal models and human subjects to exhibit tolerance to repetitive dosing, becoming less efficacious over time [ 43 45 ], while ORAs, including suvorexant (Belsomra®), have shown no tolerance or evidence of withdrawal even after a year of treatment in patients [ 17 ] and no diminution of efficacy in animal models (reviewed in [ 46 ]). While the role of orexin in reward and withdrawal suggest that ORAs may have the capacity to diminish the dependence on rewarding influences (reviewed in [ 47 ]), the effectiveness of ORAs in animal models and human subjects following treatment with the current standard of care, GABA A receptor modulators, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…or Intralipid (Vlainic and Pericic, ; Wright et al. ). For the experiment of iron chelation, DFO (100 mg/kg i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…; Gutierrez et al., ; Wright et al. ). For example, repeated DZP (a medication in the BZD family) administration increased α 1, α 4, β 1, and γ 3 subunit mRNA levels and decreased β 2 subunit mRNA levels (Holt et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In case 2, BIS exceeded 60 even at the maximum dose rate of 2 mg/kg/h of remimazolam. Several studies have identified neuroadaptive mechanisms underlying benzodiazepine tolerance including alterations in GABA-A receptor subunit mRNA expression [ 3 , 4 ]. However, the details of these mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%